Does a Patient's Approach to Achieving Goals Influence His or Her Recovery Trajectory After Musculoskeletal Illness?. Issue 9 (September 2020) - Vranceanu, Ana-Maria; Reichman, Mira; Mace, Ryan A.; Mohamadi, Amin; Chen, Neal
Abstract: Background: The regulatory focus theory posits that, in general, people tend to be predominantly "promotion focused" or "prevention focused", and each individual's values and motivations influence which approach he or she may use when pursuing personal goals. People who are primarily promotion focused mostly see goals as opportunities to gain or advance (that is, play to win); people who are prevention focused mostly see goals as opportunities to stay safe (that is, play not to lose). Understanding the role of regulatory focus in the recovery of patients with orthopaedic conditions could provide novel insight into how surgeons can best communicate with patients to improve how they recover from illness or injury. Question/purpose: Are improvements in pain intensity and disability over 6 months associated with a patient's levels of promotion focus or prevention focus? Methods: In this longitudinal observational study, we enrolled 144 patients with an upper extremity orthopaedic illness at a tertiary teaching hospital and followed them for 6 months. At baseline, patients completed validated self-reported measures of regulatory focus (Regulatory Focus Questionnaire), pain (Numerical Rating Scale), disability (the QuickDASH), and demographics. Assessments were repeated 6 months later, with 76% (110 of 144) of patients completing follow-up assessments. We examined whether regulatory focus was associated with recovery outcomes (level of pain and disability at 6 months). The patient's regulatory focus was graded as two numerical scores on separate promotion-focus and prevention-focus continuums. Each individual received a score on promotion focus and one on prevention focus.. Results: An individual's level of promotion (ΔR 2 = 0.021; p = 0.03; small effect size), but not his or her level of prevention (ΔR 2 = 0.003; p = 0.35; negligible effect size), was associated with improvement in disability over a 6-month period (R 2 = 0.61; p < 0.001). Patients with high promotion (n = 20, b = 0.284; p = 0.001) had the greatest improvements in disability after 6 months compared with patients with moderate (n = 73, b = 0.422; p < 0.001) or low (n = 17, b = 0.561; p < 0.001) promotion. The levels of promotion (b = -0.22; p = 0.09) and prevention (b = -0.04; p = 0.65) were not associated with pain over time. Conclusions: To support improvements in disability for patients with upper extremity orthopaedic conditions, surgeons' communication strategies, including explanations of diagnoses and recovery trajectories, should focus on increasing patients' level of promotion (for example, by emphasizing gains and promoting positive thinking), rather than prevention (for example, by providing reassurance and problem-solving what might go wrong). Level of Evidence: Level II, prognostic study.